Automotive global value chains in Mexico: a mirage of development? - Crossa, Mateo; Ebner, Nina (Third World Quarterly, 2020)
International monetary organisations argue the 'developing countries' should foster linkages to the world economy as a means to overcome backwardness. In this article we refute the narrative that Mexico has experienced industrial upgrading. Rather, industrial growth in Mexico over the last 40 years has been shaped by neoliberal economic policies which have turned the Mexican economy into an export-led manufacturing platform designed to supply the North American market, sustained by a precarious labour market. As a result, Mexico occupies the most labour-intensive and low value-added segments of regional production chains. To make this argument, we perform an in-depth analysis of the Mexican automotive industry, demonstrating that instead of being an engine for domestic industrial development, the auto industry has become a dominant economic sector through productive hyper-specialisation concentrated in the northern Mexican border states, a reliance on transnational capital, particularly from the United States, a disconnect with domestic markets, and the super-exploitation of labour.